Keefektifan pendekatan Problem Posing ditinjau dari keterampilan berpikir Matematis - Ahmad Nasrullah, Ahmad Nasrullah (Jurnal of Math Tadris, 2021)
This study aims to describe the effectiveness of problem posing approach in term of mathematical thinking skill of senior high school students. This study was a quasi-experimental study using the nonequivalent pretest and posttest group design. The population was year X students of State Senior High School 1 of Sakra Lombok Timur that consisted of six classes. The sample was two classes selected randomly from all Year X classes; class X-5 received a treatment of problem posing approach and class X-6 received as a control class. The instrument used is a test to measure mathematical thinking skill. To find out the effectiveness of problem posing approaches in the mathematical thinking skill, the data were analyzed using One Sample Test. The result of the study states that problem posing approach is effective in terms of the mathematical thinking skill of Senior High School Students.